PENGARUH METODE LAMA WAKTU PEMASAKAN SAGU SEP DAGING RUSA (Cervus timorensis) DENGAN CARA PENGUKUSAN DAN PENGOVENAN TERHADAP SUSUT MASAK DAN SIFAT ORGANOLEPTIK - Bonita Praptiwi Dewi; Dirwan Muchlis; Irine Ike Ike; Maria M Nay Nadu Lesik (Faculty of Agriculture, Musamus University, 2018)
The purpose of this to determine the cooking loss and organoleptic test of deer meat sago sep (Cervus timorensis) with different of cooking time. This research used a complete randomized design (RAK) which consists, 3 treatment and 3 replication. The treatment were I- C1 (cooking time for 40 minutes), treatment II-C2 (cooking time for 60 minutes) and treatment III-C3 (cooking time for 80 minutes). The parameters measured were cooking loss and organoleptic test on the aroma, color, flavor, texture and receptivity. The result of this research is cooking loss of steaming and baking on treatment C1 is better average 13,11 and 5,65 ,however based on organoleptic test, the treatment C3 preferred by panelis. The cooking time on steaming and baking give a aroma, color, flavor, texture and acceptance significant effect (P<0,05)